Thermo-economic and sensitivity analysis of a central tower hybrid Brayton solar power plant. (5th March 2021) - Merchán, R.P.; Santos, M.J.; García-Ferrero, J.; Medina, A.; Hernández, A. Calvo
Highlights: Thermo-economic records are calculated for a central tower thermosolar plant. The power unit coupled to the receiver runs a hybrid gas turbine. A plant overall model for precise sensitivity analysis is developed. Levilized cost of electricity is estimated for real climatological conditions at two different locations. Turbine inlet temperature and receiver aperture size are key parameters. Abstract: A hybrid central tower thermo-solar plant working with a gas turbine is simulated by means of an in-house developed model and software. The model considers the integration of all plant subsystems. The calculation of the heliostat solar field efficiency includes the main losses factors as blocking, shadowing, attenuation, interception, and cosine effect. The simulation considers a Brayton cycle for the power unit with irreversibilities in the compressor and turbine, and pressure drops in the heat absorption and extraction processes. A combustion chamber burning natural gas ensures an approximately constant power output. The model is flexible and precise. At the same time it is fast enough to perform sensitivity studies on the efficiency of any subsystem and the overall plant. Thus, it allows for performing a thermo-economic analysis of the plant checking the influence of the main plant design parameters. The focal objective is to analyze the importance on the levelized cost of electricity (LCoE) of the key plant design parameters. The direct influence of parameters from the heliostat field and receiver (as tower height, distance to the first row of heliostats, heliostats size, receiver size and heat losses, etc.) on final LCoE is surveyed. Similarly, parameters from the turbine as pressure ratio, turbine inlet temperature, influence of recuperation and others, are also analyzed. The dimensions of the plant are taken from SOLUGAS prototype near Seville, Spain, although another location with quite different solar conditions in Spain is also considered. LCoE values predicted are about 158 USD/MWh. The analysis concludes that among several parameters surveyed, two of them are key in LCoE predicted values: turbine inlet temperature and solar receiver aperture size.